2016
DOI: 10.1590/0034-7167-2016-0210
|View full text |Cite
|
Sign up to set email alerts
|

Colonização nasal por Staphylococcus aureus entre estudantes de Enfermagem: subsídios para monitorização

Abstract: the nasal cavity is an important bacterial flora of S. aureus in nursing students. The profile of isolated strains highlights the increase of Staphylococcus aureus resistance to antimicrobials such as oxacillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(19 reference statements)
3
3
0
3
Order By: Relevance
“…Previous studies performed with individual cohorts showed that the prevalence of nasal colonization by S. aureus and MRSA is highly variable. For instance, reported prevalence of S. aureus and MRSA carriers ranged from 12.0 to 39.8% and 0.2 to 22.6%, respectively, among healthcare workers [13,16,17,37,38], and 15.0 to 40.8% and 0 to 8.0%, respectively, among students [20,[39][40][41].…”
Section: S Aureus Nasal Carriage Was Significantly Higher Inmentioning
confidence: 99%
“…Previous studies performed with individual cohorts showed that the prevalence of nasal colonization by S. aureus and MRSA is highly variable. For instance, reported prevalence of S. aureus and MRSA carriers ranged from 12.0 to 39.8% and 0.2 to 22.6%, respectively, among healthcare workers [13,16,17,37,38], and 15.0 to 40.8% and 0 to 8.0%, respectively, among students [20,[39][40][41].…”
Section: S Aureus Nasal Carriage Was Significantly Higher Inmentioning
confidence: 99%
“…Cross-sectional studies help identify the prevalence of microorganism occurrence and its relationship with the variables, as well as aid the investigation into risk and protection factors and as such reduce the risk of infection (PAULA et al, 2018;CARVALHO et al, 2016), thus, this study aimed to describe the profile of infection by multidrug-resistant NB organisms, admitted to the neonatal intermediate care unit and the intensive care unit…”
Section: Introductionmentioning
confidence: 99%
“…Os micro-organismos estão presentes em praticamente todos os lugares, muitos são considerados patogênicos por causarem malefícios desencadeando diversas doenças. Esses seres vivos eram totalmente desconhecidos há alguns séculos e hoje são responsáveis por várias infecções e contaminações alimentares que levam muitas pessoas à morte (CARVALHO, 2016).…”
Section: Introductionunclassified
“…Se ingerido em quantidades acima do permitido pela resolução RDC nº 12, pode causar náuseas, vômitos e diarreia. O grupo dos Mesófilos é um dos mais importantes para avaliar a qualidade do produto que chega ao consumidor final, ele sugere a presença de bactérias patogênicas presentes nos alimentos derivados de carne (EVANGELISTA, 2008;LIMA et al, 2008;FERREIRA et al, 2014;CARVALHO, 2016;).…”
Section: Introductionunclassified